2015
DOI: 10.3109/13697137.2015.1007122
|View full text |Cite
|
Sign up to set email alerts
|

Is expression of rat breast matrix components influenced by estrogen, progestins and tibolone?

Abstract: There was no difference in the effects of combinations of estradiol and different progestogens on extracellular matrix components, and breast cell proliferation was associated with increases in perlecan and MMP-9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…These results points to that miR-22 can be a possible regulatory mechanism between perlecan and the ER status of the tumour. Pompei et al have shown that oestrogen pharmacologically administered to castrated rats led to an increased level of perlecan in the carotid walls [42], and in rat mammary tiss u e , e s t r a d i o l b e n z o a t e i n c o m b i n a t i o n s w i t h medroxyprogesterone acetate, induced perlecan production and increased breast tissue proliferation [43]. These reports further support that oestrogen and perlecan are connected to each other.…”
Section: Discussionmentioning
confidence: 99%
“…These results points to that miR-22 can be a possible regulatory mechanism between perlecan and the ER status of the tumour. Pompei et al have shown that oestrogen pharmacologically administered to castrated rats led to an increased level of perlecan in the carotid walls [42], and in rat mammary tiss u e , e s t r a d i o l b e n z o a t e i n c o m b i n a t i o n s w i t h medroxyprogesterone acetate, induced perlecan production and increased breast tissue proliferation [43]. These reports further support that oestrogen and perlecan are connected to each other.…”
Section: Discussionmentioning
confidence: 99%